Heterogeneous focal adhesion cytoskeleton nanoarchitectures from microengineered interfacial curvature to oversee nuclear remodeling and mechanotransduction of mesenchymal stem cells - Huayu Fan; Hui Zhao; Yan Hou; Danni Meng; Jizong Jiang; Eon-Bee Lee; Yinzheng Fu; Xiangdong Zhang; Rui Chen; Yongtao Wang (Cellular & Molecular Biology Letters)
Abstract Background Interfacial heterogeneity is widely explored to reveal molecular mechanisms of force-mediated pathways due to biased tension. However, the influence of cell density,, curvature, and interfacial heterogeneity on underlying pathways of mechanotransduction is obscure. Methods Polydimethylsiloxane (PDMS)-based stencils were micropatterned to prepare the micropores for cell culture. The colonies of human mesenchymal stem cells (hMSCs) were formed by controlling cell seeding density to investigate the influences of cell density, curvature and heterogeneity on mechanotransduction. Immunofluorescent staining of integrin, vinculin, and talin-1 was conducted to evaluate adhesion-related expression levels. Then, immunofluorescent staining of actin, actinin, and myosin was performed to detect cytoskeleton distribution, especially at the periphery. Nuclear force-sensing mechanotransduction was explained by yes-associated protein (YAP) and laminA/C analysis. Results The micropatterned colony of hMSCs demonstrated the coincident characters with engineered micropores of microstencils. The cell colony obviously developed the heterogeneous morphogenesis. Heterogeneous focal adhesion guided the development of actin, actinin, and myosin together to regulate cellular contractility and movement by integrin, vinculin, and talin-1. Cytoskeletal staining showed that actin, actinin, and myosin fibers were reorganized at the periphery of microstencils. YAP nuclear translocation and laminA/C nuclear remodeling were enhanced at the periphery by the regulation of heterogeneous focal adhesion (FA) and cytoskeleton arrangement. Conclusions The characters of the engineered clustering colony showed similar results with prepared microstencils, and colony curvature was also well adjusted to establish heterogeneous balance at the periphery of cell colony. The mechanism of curvature, spreading, and elongation was also investigated to disclose the compliance of FA and cytoskeleton along with curvature microarrays for increased nuclear force-sensing mechanotransduction. The results may provide helpful information for understanding interfacial heterogeneity and nuclear mechanotransduction of stem cells.